GAMBARAN KUALITAS HIDUP PASIEN DIABETES MELLITUS DI POLIKLINIK ENDOKRIN RSUP PROF. Dr. R. D. KANDOU MANADO - Joice M. Laoh; Debora Tampongangoy (POLTEKKES KEMENKES MANADO, 2015)
Diabetes Mellitus is a state of chronic hyperglycemia accompanied by metabolic disorders due to various hormonal disorders that cause a variety of chronic complications in the eyes, kidneys, nerves and blood vessels that can affect a person's quality of life. This study aims to describe the general quality of life of patients with diabetes mellitus in BLU Endocrine Polyclinic Hospital, Prof. Dr. R. D. Kandou Manado.This type of research is descriptive, taken by accidental sampling technique, the number of 30 respondents. The research was conducted in July 2015. The instrument used is the World Health Organization Quality of Life Instrument (WHOQOL-BREF). Results of this research is processed manually by using the formula P = (f / n) x100.The survey results revealed, the quality of life of patients with Diabetes Mellitus is in good category were 19 respondents (63.3%) and unfavorable 11 respondents (36.7%). In conclusion, the quality of life of patients with diabetes mellitus in Endocrine Polyclinic Hospital, Prof. Dr. R. D. Kandou Manado Good. Saran, is expected to be input for a nurse to be able to maintain and improve the quality of services that support interventions to maintain and improve the quality of life of patients with Diabetes Mellitus.